Circulating Th2 cell reduction and Th1/Th2 imbalance are correlated with primary Sjogren’s syndrome-associated interstitial lung disease - Lei Shi; Jia Wang; Hong-Xia Guo; Xiao-Lei Han; Yu-Ping Tang; Guang-Ying Liu (Arthritis Research & Therapy, 2022)
Abstract Objective Primary Sjogren’s syndrome (pSS) is a heterogeneous chronic autoimmune disorder characterized by lymphocyte infiltration of the exocrine glands and the involvement and dysfunction of multiple organs and tissues. Interstitial lung disease (ILD) is the most common type of respiratory system damage. This study ascertained the factors related to ILD in patients with pSS (pSS-ILD), such as altered levels of circulating lymphocyte subtypes. Methods Eighty healthy controls and 142 patients diagnosed with pSS were included. The pSS patients were classified into groups with pSS-ILD or pSS without ILD (pSS-non-ILD). Baseline clinical and laboratory data were collected for all subjects, including the levels of lymphocytes measured by modified flow cytometry. Results The pSS-ILD patients were older, had higher ESSDAI scores, had higher positivity rates for anti-SSB and anti-Ro52 antibodies, and had more frequent symptoms of respiratory system involvement than pSS-non-ILD patients. pSS-ILD patients had the lowest Th2 cell counts among the three groups. Although the absolute numbers of Treg and NK cells were lower in pSS patients with and without ILD than in the healthy controls, there was no significant difference between the two pSS groups. The Th1/Th2 ratio was significantly higher in patients with ILD than in patients without ILD. Further analysis showed that older age (OR=1.084), lower Th2 count (OR=0.947), higher Th1/Th2 ratio (OR=1.021), and positivity for anti-SSB (OR=3.620) and anti-Ro52 (OR=5.184) antibodies were associated with the occurrence of ILD in patients with pSS. Conclusion Decreased circulating Th2 cells and an elevated Th1/Th2 ratio may be the immunological mechanism underlying the development of ILD in pSS patients.